Legal Ramifications of Employing AI-Generated Logos as Brand Identities: A Juridical Examination - Pratama, Muh Ersandi Rizki; Bimantara, Sandy Erdi; Samantha, Giovanni (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2024)
The utilization of Artificial Intelligence (AI) technology is experiencing rapid expansion in contemporary times. Within the domain of trademark law, a logo serves as a visual identity utilized to distinguish a product or service from its competitors. The utilization of a logo as a brand identity is afforded specific legal protections pursuant to Indonesian Law No. 20/2016 concerning Trademarks. A pivotal consideration pertains to discerning the rightful owner of the rights to the logo created by AI. Is it the proprietor of the AI software employed in crafting the logo, or is it the proprietor of the company or individual who commissioned the logo? The method employed in this research is a normative juridical approach, which scrutinizes the application of legal principles or norms. The approaches employed in this research encompass conceptual and statutory analyses. The objective of this research pertains to understanding the Legal Implications of Utilizing Artificial Intelligence-Generated Logos as Brand Identities, and serving as a reference material for subsequent legal inquiries, particularly those related to the advancement of artificial intelligence. The majority of regulations concerning copyright and ownership of artistic works still hinge upon Copyright Law No. 28/2014. Despite its enactment, the Copyright Law remains bereft of provisions safeguarding works generated by Artificial Intelligence. In the realm of AI or artificial intelligence, there are instances where AI applications inadvertently generate trademark logos bearing visual resemblance to other trademark logos. Such resemblances have the potential to bewilder consumers and undermine the authenticity of a brand.